Iron-doped cobalt nitride nanoparticles (Fe–Co3N): An efficient electrocatalyst for water oxidation. (6th January 2021) - Wu, Liqian; Shi, Dongdong; Yan, Shiming; Qiao, Wen; Zhong, Wei; Du, Youwei
Abstract: The exploration of efficient, low-cost and earth-abundant oxygen-evolution reaction (OER) electrocatalysts and the understanding of the intrinsic mechanism are important to advance the clean energy conversion technique based on electrochemical water oxidation. In this work, Fe-doping Co3 N catalysts were successfully synthesized by a simple nitridation reaction of the Co3- x Fe x O4 precursor. This material exhibited a low overpotential of 294 mV at a current density of 10 mA cm −2, and a small Tafel slope of 49 mV dec −1 in 1 M KOH solution, superior to the performance of Co3 N and IrO2 . As revealed by the spectroscopic and electrochemical analyses, the enhanced OER performance mainly originates from the electronic modulation induced by the incorporation of Fe into Co3 N, benefitting the formation of CoOOH as active surface species and thus facilitating the OER process. These findings also demonstrate the introduction of heterogeneous element is a simple and effective strategy to regulate the OER property of the cobalt nitrides (Co3 N) catalysts. Graphical abstract: Image 1 Highlights: It is the first report to research Fe-doping Co3 N as OER catalysts. Fe-doping catalysts exhibited superior performance than Co3 N and IrO2 . The enhanced activity of OER is mainly due to the Fe inducing electronic modulation.